Isolable 1‐Butene Copper(I) Complexes and 1‐Butene/Butane Separation Using Structurally Adaptable Copper Pyrazolates. Issue 3 (10th December 2020) - Elashkar, Ahmed H.; Parasar, Devaborniny; Muñoz‐Castro, Alvaro; Doherty, Cara M.; Cowan, Matthew G.; Dias, H. V. Rasika
Abstract: Non‐porous small molecule adsorbents such as {[3, 5‐(CF3 )2 Pz]Cu}3 (where Pz=pyrazolate) are an emerging class of materials that display attractive features for ethene−ethane separation. This work examines the chemistry of fluorinated copper(I) pyrazolates {[3, 5‐(CF3 )2 Pz]Cu}3 and {[4‐Br‐3, 5‐(CF3 )2 Pz]Cu}3 with much larger 1‐butene in both solution and solid state, and reports the isolation of rare 1‐butene complexes of copper(I), {[3, 5‐(CF3 )2 Pz]Cu(H2 C=CHC2 H5 )}2 and {[4‐Br‐3, 5‐(CF3 )2 Pz]Cu(H2 C=CHC2 H5 )}2 and their structural, spectroscopic, and computational data. The copper−butene adduct formation in solution involves olefin‐induced structural transformation of trinuclear copper(I) pyrazolates to dinuclear mixed‐ligand systems. Remarkably, larger 1‐butene is able to penetrate the dense solid material and to coordinate with copper(I) ions at high molar occupancy. A comparison to analogous ethene and propene complexes of copper(I) is also provided. Abstract : Adsorbed by a trinuclear complex : Butene‐induced structure reorganization process of trinuclear copper complexes has led to isolable, dinuclear copper(I) complexes of 1‐butene in solution. These large molecules also penetrate solid non‐porous copper pyrazolate materials forming copper−olefin complexes.